The Development of the Judiciary in the UK: An Analytical Study. - Tahroui, Sara; Loulou, Saida (جامعة الوادي - University of Eloued, 2023)
This research attempts to conduct an analytical study in order to investigate the development process of the judiciary system in the United Kingdom. In order to conduct this study, three questions have been asked. The first question inquiries on the features that characterize the United Kingdom judicial system before the Constitutional Reform Act of 2005. The second examines the characteristics, which distinguish the new United Kingdom judicial system from the one preceding the reforms. The third seeks to identify the extent of independence allocated to the Judiciary by these reforms. To respond to the previously asked questions, three hypotheses have been formulated .The first proposes that the implementation of the laws of the United Kingdom judicial system before 2005 could lead to a limited independence of the system, and a significant role to the House of Lords. The second hypothesis indicates that the peculiarities of the Constitutional Reform Act 2005 made radical changes in the United Kingdom judiciary system. The third hypothesizes that the implementation of the Constitutional Reforms laws offered more independence to the judicial system from the executive and legislative. In order to investigate the validity of our hypotheses, we used the historical-analytical and comparative methods. The findings of the study revealed that the United Kingdom judiciary system, before the Constitutional Reforms, was subject to the will of monarchs. The Constitutional Reform Act 2005 brought radical changes, including the establishment of a Supreme Court, the abolishment of the House of Lords' jurisdictional power, weakening the position of the Lord Chancellor, and the creation of an Independent Judicial Appointments Commission. Consequently, the United Kingdom judiciary system became more powerful, more independent and more authoritative. يحاول هذا البحث إجراء دراسة تحليلية لإستقصاء عملية تطور النظام القضائي في المملكة المتحدة. و من أجل إجراء هذه الدراسة ، فقد تم طرح ثلاثة أسئلة مختلفة. فأما السؤال الاول فإنه يستفسر عن خصائص النظام القضائي في المملكة المتحدة قبل قانون الإصلاح الدستوري لعام 2005 . . بينما يفحص السؤال الثاني خصائص ومميزات النظام القضائي البريطاني بعد قانون الإصلاح الدستوري لعام 2005 . و السؤال الثالث بدوره يختبر مدى تأثير قانون الإصلاح الدستوري على النظام القضائي في المملكة المتحدة . و للإجابة عن الأسئلة المطروحة سابقا ، تمت صياغة ثلاث فرضيات . الفرضية الأولى تقترح أن فحص النظام القضائي البريطاني قبل عام 2005 يمكن أن يؤدي إلى استقلال محدود للنظام ، و دور مهم لمجلس اللوردات. و أما الفرضية الثانية فإنها تشير إلى أن خصائص قانون الإصلاح الدستوري يمكن أن تحدث تغييرات جذرية في النظام القضائي في المملكة المتحدة . أما الفرضية الثالثة فإنها تتعلق بتحليل الكيفية التي يحفز بها قانون الإصلاح الدستوري النظام القضائي البريطاني ليكون أكثر إستقلالية و ذو سلطة. و من أجل التحقق من صحة فرضياتنا ، فقد إتبعنا كلا من الأساليب التاريخية ، التحليلية و المقارنة. و عليه فقد كشفت الدراسة عن النتائج التالية : كان النظام القضائي البريطاني قبل قانون الإصلاح الدستوري نظاماً ضعيفا ، خاضعا و تابعا لسلطة الملوك و من ثم لسلطة البرلمان . و لكن عقب الإصلاحات الدستورية لعام 2005 ، حدثت عدة تغييرات و إصلاحات جذرية له ، بما في ذلك إنشاء محكمة عليا منفصلة ، إلغاء السلطة القضائية لمجلس اللوردات ، تعديل دور اللورد المستشار و مكتبه ، إضافة إلى إنشاء لجنة تعيينات قضائية مستقلة ، و نتيجة لذلك فقد أصبح النظام القضائي في المملكة المتحدة أكثر قوة و استقلالية و ذا سلطة و نفوذ على غير ما كان عليه سابق
Keywords: The Constitutional Reform Act, The House of Lords, the Judiciary, the Lord Chancellor.; مجلس اللوردات , اللورد المستشار , القضاء, قانون الاصلاح الدستوري.